Correlation and Path Analysis in Sesamum (Sesamum indicum L.) under Rainfed Conditions - Kuriakose Conil (Department of Plant Breeding, College of Agriculture, 1991)
A research programme was carried out at the College of Agriculture, Vellayani with twentyfive varieties of sesamum during the rabi season of 1989, in order to identify superior sesamum genotypes possessing high oil content and to asses the relationship between yield oil content and to assess the relationship between yield and other plant characters through correlation and path analysis under rainfed conditions in the rabi uplands. The design adopted was a randomised block design with three replications and observations were recorded from randomly tagged plants on 13 plant characters and the major weather parameters. Significant differences existed among varieties with respect to six characters studied. The variety C-6 had the maximum seed oil percentage of 56.96 per cent. The variation in oil content of seeds was largely due to genotypic differences. The highest estimate of 94 per cent heritability was shown by the character oil content of seeds, while the highest genetic advance under 5 per cent selection was shown by the character number of seeds per capsule. At the genotypic level, seed yield was positively correlated with plant height, length of the capsule, breadth of the capsule, root-shoot ratio, number of seeds per capsule, days to first flowering and oil content of seeds and negatively with number of leaves per plant and number of capsules per plant. The oil content of seeds showed positive genotypic correlations with number of seeds per capsule, days to first flowering and seed yield and a negative correlation with root- shoot ratio. Path analysis technique was not found to be satisfactory to explain the direct and indirect effects of plant characters since the residual values obtained were high. The variety ACV-2 ranked first among the five varieties identified as superior genotypes at 20 per cent selection. The expected genetic gain was estimated as 37.25. The maximum amount of drymatter was produced by the variety ACV-1. The variety NPG-3 had the highest amount of proline in its leaves. None of the varieties could be regarded as a 'proline accumulating' genotype. The highest percentage of soil moisture available was at 56 days after sowing. The sesamum crop received the highest amount of 25.5 mm rainfall during the 42nd standard meterological week and the lowest amount of 1 mm rainfall during the 50th standard meterological week.